City Centered Cycling - Reilly, Lyle (Auckland University of Technology, 2009)
This project explores design considerations and processes involved in the development of sports performance clothing specifically aimed at city cycling commuters. Research with a focus on smart clothing and electronic integration was used to form a technical framework in which the requirements of the end user were addressed. The result being the creation of a wearable electronic jacket containing a lighting system aimed at improving safety and comfort aspects affecting cycle commuters. The project methodology was essentially practice based with a strong experimental approach linked to the physical testing and refinement of electronic and clothing integration. Design aesthetics were equally important and are presented as a visual record linked to the use of computer related technologies which have influenced the design planning and processes of the project.
Keywords: Wearable electronics; Sports fashion; Cycling; Performance sportswear